The Role of External Auditors in Client Tax Compliance : A Case Study at Budiandru & Partners Public Accounting Firm - Fauziah Tiara Anggraini; Zul Azmi (UNIB Press, 2025)
Taxes constitute a primary source of state revenue and play a crucial role in national development and the improvement of public welfare. However, tax compliance in Indonesia remains relatively low, as reflected in the suboptimal tax ratio. One effort to enhance tax compliance is through the involvement of external auditors. This study aims to examine the role of external audits in improving client tax compliance. A qualitative descriptive method was employed, using purposive sampling to select five senior auditors who were interviewed through semi-structured interviews conducted in July 2025 at Budiandru & Partners Public Accounting Firm, located in Pekanbaru City. The findings indicate that external audits contribute to helping clients prepare credible financial statements, understand the tax system, and encourage honesty and transparency in tax reporting. Audits also enhance clients' tax knowledge, play an indirect role in the dissemination of tax regulations, foster awareness and responsibility toward tax obligations, increase alertness to potential sanctions, and promote transparency. In the context of tax modernization, auditors also assist clients in adapting to digital systems, although technical challenges are still encountered..